Analysis Of Comfort Factors, Tariffs And Timeliness Of Train Ticket Purchases Majoring In Medan-Binjai - Lina Litafia; Nursiah Fitri; Ratna Dewi (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
This study aims to determine whether the factors of comfort, tariffs and timeliness of purchasing decisions simultaneously have a positive and significant effect on customer satisfaction on trains majoring in Medan Binjai. The data analysis technique used is the method with the help of the SPSS program. This study uses multiple linear regression. The sample of this study amounted to 100 respondents. Primary data collection using a questionnaire. The results showed that convenience, tariffs and timeliness partially had a positive and significant effect on purchasing decisions for train tickets majoring in Medan-Binjai. In addition, convenience, tariffs and punctuality simultaneously have a positive and significant effect on purchasing decisions for train tickets majoring in Medan-Binjai.